Random Search Walks Inside Absorbing Annuli - Anderson S. Bibiano-Filho; Jandson F. O. de Freitas; Marcos G. E. da Luz; Gandhimohan M. Viswanathan; Ernesto P. Raposo (Entropy)
We revisit the problem of random search walks in the two-dimensional (2D) space between concentric absorbing annuli, in which a searcher performs random steps until finding either the inner or the outer ring. By considering step lengths drawn from a power-law distribution, we obtain the exact analytical result for the search efficiency <semantics>η</semantics> in the ballistic limit, as well as an approximate expression for <semantics>η</semantics> in the regime of searches starting far away from both rings, and the scaling behavior of <semantics>η</semantics> for very small initial distances to the inner ring. Our numerical results show good overall agreement with the theoretical findings. We also analyze numerically the absorbing probabilities related to the encounter of the inner and outer rings and the associated Shannon entropy. The power-law exponent marking the crossing of such probabilities (equiprobability) and the maximum entropy condition grows logarithmically with the starting distance. Random search walks inside absorbing annuli are relevant, since they represent a mean-field approach to conventional random searches in 2D, which is still an open problem with important applications in various fields.